Effect of Nitriding Time on the Structural Evolution and Properties of Austenitic Stainless Steel Nitrided Using High Power Pulsed DC Glow Discharge Ar/N2 Plasma - Yang, S.; Kitchen, M.; Luo, Q.; Ievlev, D.N.; Cooke, K.E. (Journal of Coating Science and Technology, 2016)
A high power pulsed DC glow discharge plasma (HPPGDP) system was employed to perform fast nitriding of AISI 316 austenitic stainless steel in Ar and N2 atmosphere. In-situ optical emission spectroscopy and Infrared pyrometer measurements were used during the plasma nitriding to investigate the effect of dynamic plasma on the nitriding behaviour. SEM and EDX, XRD, Knoop indentation, and tribo-tests were used to characterise microstructures and properties of the nitrided austenitic stainless steel samples. HPPGDP produced high ionization of both Ar and N2 in the plasma that corresponded to dense ion bombardment on the biased steel samples to induce effective plasma surface heating and to form high nitrogen concentration on the biased steel surfaces, and therefore fast nitriding (> 10µm/hour) was achieved. Various phases were identified on the nitrided stainless steel samples formed from a predominantly a single phase of nitrogen supersaturated austenite to a multi-phase structure comprising chromium nitride, iron nitride and ferrite dependent on the nitriding time. All the nitrided AISI 316 austenitic stainless steel samples were evaluated with high hardness (up to 17.3 GPa) and exceptional sliding wear resistance against hardened steel balls and tungsten carbide balls.